Ultrastructural changes in the oocytes and hepatocytes associated with the maturation of gonads in the protogynous spinycheek grouper, Epinephelus diacanthus (Valenciennes) - Rao, A. Chandrasekhara; Krishnan, L.; Sanil, N. K. (Indian Journal of Fisheries, 2013)
Ultrastructural changes in the oocytes and hepatocytes in the female Epinephelus diacanthus were studied with the progress of maturation. Transmission electron microscopic (TEM) observations revealed cytological changes associated with ovarian development. Nucleolus number increased in the perinucleolus stage, which is an indirect indication of increase in protein synthesis with the onset of oogenesis. Zonation of yolk sphere and presence of microvilli in the zona radiata were observed in mature oocytes. In comparison to the immature phase, mature/ripe satge hepatocytes showed greater development of both endoplasmic reticulum and increased density of mitochondria in the cytoplasm which is an evidence of progress in vitellogenin synthesis.